Ethiopia adopts WLE/IWMI suggestions on valuing multiple uses of water in its new water policy - CGIAR Research Program on Water, Land and Ecosystems (2020)
WLE/IWMI worked with the Ministries of Agriculture and of Water, Irrigation and Electricity to contribute to policy review processes, leading to draft policy document on irrigation.